Grain-oriented electrical steel sheet

By controlling the amounts of Co and Ti in the base steel sheet and forsterite coating, the grain-oriented electrical steel sheet achieves reduced building factors and improved magnetic properties, addressing the discrepancy between material and transformer core iron loss.

JP7601280B2Active Publication Date: 2024-12-17JFE STEEL CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024514751
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-09-09
Filing Date
2023-09-04
Publication Date
2024-12-17
Estimated Expiration
2043-09-04

AI Technical Summary

Technical Problem

Grain-oriented electrical steel sheets used in transformers exhibit a discrepancy between the iron loss value of the material and the transformer core, leading to high building factors that hinder achieving sufficient performance, particularly in the context of carbon neutrality where reducing iron loss in the final product is crucial.

Method used

Control the amounts of Co and Ti in the base steel sheet and the forsterite coating to achieve a specific ratio of hysteresis loss to iron loss, ensuring the grain-oriented electrical steel sheet meets the criteria 0.30≦R17≦R19, thereby reducing the building factor.

Benefits of technology

The proposed solution effectively reduces the building factor, enhancing the magnetic properties of the steel sheet and improving transformer characteristics by optimizing the magnetic flux distribution and minimizing eddy current losses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601280000004
    Figure 0007601280000004
  • Figure 0007601280000005
    Figure 0007601280000005
  • Figure 0007601280000006
    Figure 0007601280000006
Patent Text Reader

Abstract

Provided is a grain-oriented electromagnetic steel sheet having such a magnetic property that a building factor can be reduced satisfactorily. The grain-oriented electromagnetic steel sheet comprises a matrix steel sheet containing 1.50 to 8.00% by mass of Si, 0.02 to 1.00% by mass of Mn and 0.005 to 0.050% by mass of Co and a base coating film formed on the surface of the matrix steel sheet and containing forsterite as a main ingredient, in which the amount of Ti relative to the total amount of the matrix steel sheet and the base coating film is 0.0050 to 0.0200% by mass, and the formula: 0.30≦R17≦R19 is satisfied in which R17 represents a ratio of iron loss W17 / 50 to hysteresis loss Wh17, i.e., W17 / 50 / Wh17, when the grain-oriented electromagnetic steel sheet is excited at 1.7 T and R19 represents a ratio of iron loss W19 / 50 to hysteresis loss Wh19, i.e., W19 / 50 / Wh19, when the grain-oriented electromagnetic steel sheet is excited at 1.9 T.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a grain-oriented electrical steel sheet suitable for use as a transformer core material. [Background technology]

[0002] Grain-oriented electrical steel is a soft magnetic material used as the iron core material of transformers. <001> This type of texture is characterized by the crystal structure having a highly aligned orientation in the rolling direction of the steel sheet. During the purification annealing process in the manufacturing process of grain-oriented electrical steel sheets, the {110} <001> It is formed through a phenomenon called secondary recrystallization, which causes preferential giant growth of crystal grains in a certain orientation.

[0003] Regarding this formation method, a commonly used technique is to use a precipitate called an inhibitor to cause secondary recrystallization of grains having the Goss orientation during purification annealing. For example, the method using AlN and MnS described in Patent Document 1 and the method using MnS and MnSe described in Patent Document 2 have been industrially put into practical use.

[0004] The method using these inhibitors is useful for stably developing secondary recrystallized grains, but in order to finely disperse the inhibitors in the steel, it is necessary to heat the slab at high temperatures of 1300°C or higher and dissolve the inhibitor components in the steel.

[0005] On the other hand, a technique for developing Goss-oriented crystal grains by secondary recrystallization in a material that does not contain inhibitor components is disclosed in Patent Document 3 and the like. This is a technique for secondary recrystallization of grains having Goss orientation without using an inhibitor by eliminating impurities such as inhibitor components as much as possible, thereby making the grain boundary energy dependency on the grain boundary misorientation angle that the grain boundary has during primary recrystallization apparent, and this effect is called the texture inhibition effect. This method does not require fine dispersion of inhibitors in the steel, and therefore does not require slab heating at high temperatures, which was previously essential, and has great advantages in terms of cost and maintenance.

[0006] Grain-oriented electrical steel sheets are mainly used as transformer cores, and are required to have excellent magnetization characteristics, especially low iron loss. To achieve this, it is important to highly align the secondary recrystallized grains in the steel sheet to the Goss orientation and to reduce impurities in the product sheet. In addition, a technology has been developed to introduce nonuniformity into the surface of the steel sheet by a physical method, subdivide the width of the magnetic domain, and reduce the iron loss, that is, a magnetic domain subdivision technology. For example, Patent Document 4 proposes a technology to reduce the iron loss of the steel sheet by irradiating the final product sheet with a laser, introducing a high dislocation density region into the surface layer of the steel sheet, and narrowing the magnetic domain width. In addition, Patent Document 5 proposes a technology to control the magnetic domain width by irradiating it with an electron beam.

[0007] Highly aligning the orientation after secondary recrystallization to the Goss orientation and reducing impurities in the product sheet reduces hysteresis loss, whereas application of magnetic domain refinement technology primarily reduces eddy current loss. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Special Publication No. 40-15644 [Patent Document 2] Special Publication No. 51-13469 [Patent Document 3] JP 2000-129356 A [Patent Document 4] Special Publication No. 57-2252 [Patent Document 5] Special Publication No. 6-72266 Summary of the Invention [Problem to be solved by the invention]

[0009] As mentioned above, grain-oriented electromagnetic steel sheets are mainly used as the iron core of transformers. Generally, there is a discrepancy between the iron loss value of a transformer core and the iron loss value of the grain-oriented electromagnetic steel sheet that is the material, with the iron loss of the transformer core being greater. The iron loss ratio between the two (the iron loss of the transformer core divided by the iron loss value of the material) is called the building factor. In other words, even if the iron loss of the material is good, if the building factor is high, the iron loss of the transformer core will be large, resulting in a problem of insufficient performance. In the carbon-neutral era, what needs to be reduced is the iron loss of the final product, the transformer, and no matter how low the iron loss of the material is, it is meaningless if the building factor is high. The building factor affects not only the design of the transformer but also the characteristics of the material, so there is a demand to lower the building factor along with the iron loss of the material.

[0010] That is, an object of the present invention is to provide a grain-oriented electrical steel sheet having magnetic properties that can sufficiently reduce the building factor. [Means for solving the problem]

[0011] As a result of extensive research, the inventors have discovered that it is possible to produce a grain-oriented electrical steel sheet that achieves a low building factor by controlling, within certain ranges, the amount of Co in the base steel sheet on which a base coating mainly composed of forsterite is formed, and the amount of Ti in the grain-oriented electrical steel sheet on which the base coating is formed.

[0012] The experiments that led to the success of the present invention are described below. <Experiment 1> In order to mainly change the Co content, the steel slabs were produced by continuous casting, containing, by mass%, C: 0.050-0.081%, Si: 3.15-3.31%, Mn: 0.07-0.10%, Al: 0.020-0.025%, N: 0.0069-0.0085%, S: 0.0011-0.0031%, Sb: 0.025-0.036%, Co: 0-0.123%, and Ti: 0.0080-0.0090%, with the balance being Fe and unavoidable impurities. The slabs were then heated at 1400°C for 20 minutes, and then hot-rolled to a thickness of 2.4 mm. The slabs were then annealed at 1000°C for 30 seconds in a N2 atmosphere. Next, the steel sheet was cold-rolled to a thickness of 1.5 mm, and then intermediate annealed at 1000°C for 100 seconds in a 25%H2-75%N2 atmosphere. After that, the steel sheet was cold-rolled to a thickness of 0.23 mm, and decarburization annealed at 850°C for 150 seconds in a 50%H2-50%N2, dew point 50°C, moist atmosphere. Next, an annealing separator mainly composed of MgO was applied to the surface of the base steel sheet after decarburization annealing, and purification annealing was performed by holding at 1200°C for 10 hours. At this time, the heating rate up to 1200°C was 20°C / h, and further, during the heating process, the N2 atmosphere was used from room temperature to 700°C, the atmosphere from 700°C to 1100°C was changed to various mixture ratios of N2 and H2, and the H2 atmosphere was used from 1100°C to 1200°C. The holding atmosphere was H2, and the cooling atmosphere was Ar. In this manner, a sample was obtained in which a base coating mainly composed of forsterite (hereinafter, sometimes referred to as a forsterite coating) was formed on the surface of the base steel sheet.

[0013] For the samples thus obtained, the iron loss W 17 / 50 (Iron loss when excited up to 1.7T at 50Hz) and W 19 / 50 (Iron loss when excited up to 1.9T at 50Hz) and hysteresis loss Wh 17 (Hysteresis loss when excited up to 1.7T) and Wh 19 (Hysteresis loss when excited up to 1.9 T) was measured using the method specified in JIS C2550-1.

[0014] In addition, in order to measure the Co content in the base steel plate, a part of the obtained sample was immersed in a 10% hydrochloric acid aqueous solution at 80°C for 180 seconds to remove the forsterite coating, and the Co content was measured by the method specified in JIS G1222.

[0015] Next, a three-phase three-leg model transformer was created from the obtained sample, with an external shape of 500 mm square and a plate width of 100 mm for each leg and each yoke. The iron loss of the model transformer W 17 / 50 The iron loss of the model transformer was measured (when excited to 1.7T at 50Hz). The number of laminated samples was 50, with two laminated sheets stacked alternately. The building factor F17 of the model transformer was calculated by multiplying the iron loss of the model transformer by WT 17 / 50 The iron loss of the sample W 17 / 50 Divided by (WT 17 / 50 / W 17 / 50 The relationship between the building factor F17 and the Co content in the base steel sheet is shown in FIG.

[0016] From the results shown in Figure 1, no clear correlation was observed between the building factor F17 and the amount of Co. However, it can be seen from Figure 1 that the building factor F17 is divided into two groups: good values ​​of 1.25 or less, and high values ​​of 1.30 or more.

[0017] Therefore, we investigated whether this difference could be explained by the relationship between the iron loss and hysteresis loss of the sample. As a result, the iron loss W 17 / 50 Hysteresis loss Wh 17 Ratio of Wh 17 / W 17 / 50 When R17 is used and excitation is at 1.9T, the iron loss W 19 / 50 Hysteresis loss Wh 19 Ratio of Wh 19 / W 19 / 50 When R19 is taken as the relationship, we found that the data can be divided into Group A, which has a relationship of 0.30≦R17≦R19, and Group B, which is the rest. Figure 2 shows the result of extracting only Group A from the data in Figure 1 and redrawing it.

[0018] From the results shown in FIG. 2, it can be seen that the alloy belongs to group A, that is, has the relationship of 0.30≦R17≦R19, and exhibits a favorable building factor of 1.25 or less when the Co content is in the range of 0.005 to 0.050%.

[0019] <Experiment 2> The steel slab, which contains, by mass%, C: 0.037%, Si: 3.05%, Mn: 0.18%, Al: 0.009%, N: 0.0036%, Se: 0.007%, Sn: 0.062%, and Co: 0.0080%, with the balance being Fe and unavoidable impurities, was produced by continuous casting, and after slab heating at 1300°C for 30 minutes, it was finished to a thickness of 2.2 mm by hot rolling. Then, it was annealed at 1100°C for 30 seconds in a N2 atmosphere. Next, it was cold rolled to a thickness of 0.23 mm, and further decarburization annealing was performed at 840°C for 120 seconds in a moist atmosphere of 40% H2-60% N2 with a dew point of 40°C. Next, an annealing separator in which TiO2 was mixed in various amounts in the range of 0 to 15 parts by mass relative to MgO was applied to the surface of the base steel sheet after decarburization annealing, and purification annealing was performed by holding at 1220°C for 5 hours. At this time, the heating rate up to 1220°C was 15°C / h, and further, in the heating process, an N2 atmosphere was used from room temperature to 700°C, an atmosphere with variously changed N2 and H2 mixing ratios was used from 700°C to 1100°C, and an H2 atmosphere was used from 1100°C to 1220°C. In addition, an H2 atmosphere was used during holding, and an Ar atmosphere was used during cooling. In this way, a sample was obtained in which a base coating mainly composed of forsterite (hereinafter sometimes referred to as a forsterite coating) was formed on the surface of the base steel sheet.

[0020] For the samples thus obtained, the iron loss W 17 / 50 and W 19 / 50 and hysteresis loss Wh 17 and Wh 19 and were measured according to the method specified in JIS C2550-1.

[0021] Moreover, the Ti content in the steel sheet having the forsterite film was measured by the method specified in JIS G1223.

[0022] Furthermore, in order to measure the Co content in the base steel plate, a part of the obtained sample was immersed in a 10% hydrochloric acid solution at 80°C for 180 seconds to remove the forsterite film, and the Co content was measured by the method specified in JIS G1222. As a result, the Co content was 0.0080%, which was the same as the content in the steel slab.

[0023] Furthermore, as in experiment 1, the iron loss W 17 / 50 Hysteresis loss Wh 17 Ratio of Wh 17 / W 17 / 50 When R17 is used and excitation is at 1.9T, the iron loss W 19 / 50 Hysteresis loss Wh 19 Ratio of Wh 19 / W 19 / 50 With R19 as the value, the steel sheets are divided into Group A where the relationship is 0.30≦R17≦R19, and Group B where the other relationship is the rest. Figure 3 shows the relationship between the Ti content in steel sheets with a forsterite film and whether they belong to Group A or Group B.

[0024] From the results shown in FIG. 3, it can be seen that when the Ti content in the steel sheet having a forsterite film is 0.0039% or more and 0.0200% or less, there is a tendency for the steel sheet to belong to group A.

[0025] In addition, as in Experiment 1, a three-phase three-leg model transformer was fabricated with an external dimension of 500 mm square and a plate width of 100 mm for each leg and each yoke, and the iron loss of the model transformer W 17 / 50 (Transformer iron loss when excited to 1.7T at 50Hz) was measured. The building factor F17 of the model transformer was then calculated using the model transformer iron loss WT 17 / 50 The iron loss of the sample W 17 / 50 Divided by (WT 17 / 50 / W 17 / 50 The relationship between the building factor F17 and the Ti content in the steel sheet having a forsterite film is shown in FIG.

[0026] From the results shown in Fig. 4, it can be seen that when the Ti content of the steel sheet having a forsterite coating is less than 0.0050%, the Building Factor F17 is high even if the steel sheet belongs to group A. In summary, it was found that when the Ti content of the steel sheet having a forsterite coating is 0.0050 to 0.0200%, the Building Factor is low and good. This means that it is good for a certain amount of Ti to be present in the forsterite coating.

[0027] As described above, the mechanism by which the building factor of a model transformer is improved depending on the amount of Co in the base steel sheet and the amount of Ti in the steel sheet having a base coating mainly composed of forsterite is not clear, but the inventors believe it to be as follows. That is, because the yoke and legs of the transformer have a certain width, the magnetic path has different distances on the inside and outside, like an athletics track. For this reason, during excitation, the magnetic flux tends to be biased to the inside where the magnetic path is shorter. Even when the entire steel plate is excited to 1.7 T, the magnetic flux density on the inside exceeds that. Therefore, it is presumed that the more advantageous the high magnetic field characteristics are, the better the transformer characteristics such as the building factor will be. When Co is dissolved in iron, the saturation magnetic flux density of the iron increases, which is expected to improve the high magnetic field characteristics, and therefore it is presumed that the building factor has improved. However, throughout Experiments 1 and 2, there were two cases where the building factor was poor, even when Co was added.

[0028] The first point is the iron loss W when excited at 1.7T. 17 / 50 Hysteresis loss Wh 17 Ratio of Wh 17 / W 17 / 50 , i.e. R17 and the iron loss W when excited at 1.9T 19 / 50 Hysteresis loss Wh 19 Ratio of Wh 19 / W 19 / 50, that is, when R17 and R19 do not satisfy the relationship 0.30≦R17≦R19. A detailed investigation revealed that in most cases R17 was below 0.30. Hysteresis loss has a high correlation with B8, and since it is thought that there would be no large fluctuations for the same B8, the above is thought to be a case where eddy current loss is extremely large. In transformers, even when excited with a sine wave, high frequency components are superimposed and the waveform is distorted, which is thought to increase eddy current loss, which is highly frequency-dependent. Therefore, it is thought that a high eddy current loss ratio increases the building factor.

[0029] The second point is when the Ti content in the steel sheet with a forsterite coating is less than 0.0050 mass% or more than 0.0200 mass%. Although it is speculated, it is thought that the presence of a certain amount of Ti in the forsterite coating improves the coating properties. For example, if the coating tension is improved, the magnetic domains become finer, which may reduce eddy current loss. In that case, the eddy current loss ratio decreases, in contrast to the above cases of R17 and R19, so it is thought that the building factor can be reduced.

[0030] Incidentally, JP 2021-509149 A discloses a manufacturing technology for grain-oriented electrical steel sheets containing Co. However, this document mentions a technology for improving the magnetic properties of the electrical steel sheet itself, and this technology is completely different from the present invention in which the building factor is reduced by using a technology for including Ti in the forsterite coating in combination.

[0031] The present invention is based on the above findings. That is, the gist and configuration of the present invention are as follows.

[0032] 1. A grain-oriented electrical steel sheet comprising a base steel sheet containing 1.50 to 8.00 mass% Si, 0.02 to 1.00 mass% Mn, and 0.005 to 0.050 mass% Co, and a base coating containing forsterite as a main component formed on the surface of the base steel sheet, the Ti content in the base steel sheet and the undercoating as a whole is 0.0050 to 0.0200 mass%, Iron loss W when excited at 1.7T 17 / 50 Hysteresis loss Wh 17 Ratio of Wh 17 / W 17 / 50 When R17 is used and excitation is at 1.9T, the iron loss W 19 / 50 Hysteresis loss Wh 19 Ratio of Wh 19 / W 19 / 50 Grain-oriented electrical steel sheet that satisfies the following formula (1), where R is R19. 0.30≦R17≦R19 (1)

[0033] 2. The grain-oriented electrical steel sheet according to 1 above, wherein the Ti content in the base steel sheet is 0.0030 mass % or less.

[0034] 3. The grain-oriented electrical steel sheet according to 1 or 2 above, further comprising an insulating coating on the surface of the base coating.

[0035] 4. The grain-oriented electrical steel sheet according to any one of 1 to 3 above, wherein the base steel sheet further contains one or more elements selected from Sn: 0.500 mass% or less, Cr: 0.500 mass% or less, Cu: 0.50 mass% or less, Ni: 0.50 mass% or less, Bi: 0.500 mass% or less, P: 0.500 mass% or less, Sb: 0.500 mass% or less, Mo: 0.500 mass% or less, B: 25.0 mass ppm or less, Nb: 0.020 mass% or less, V: 0.020 mass% or less, As: 0.0200 mass% or less, Zn: 0.020 mass% or less, Pb: 0.0100 mass% or less, W: 0.0100 mass% or less, Ga: 0.0050 mass% or less, and Ge: 0.0050 mass% or less. Effect of the Invention

[0036] According to the present invention, it is possible to provide a grain-oriented electrical steel sheet having magnetic properties that can sufficiently reduce the building factor. [Brief description of the drawings]

[0037] [Figure 1]1 is a graph showing the relationship between the Co content of the base steel plate and the building factor F17 for Experiment 1. [Diagram 2] 1 is a graph showing the relationship between the Co content of the base steel plate and the building factor F17 for Experiment 1 (only Group A is extracted). [Diagram 3] 1 is a graph showing the relationship between the Ti content in a steel sheet having a forsterite film and whether the steel sheet belongs to group A or group B, in Experiment 2. [Figure 4] 1 is a graph showing the relationship between the Ti content and the building factor F17 of a steel plate having a forsterite film, relating to Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0038] Next, the reasons for limiting the constituent elements of the present invention will be described. First, the amount of each element (composition) in the base steel sheet of the grain-oriented electrical steel sheet of the present invention will be described. Note that "%" and "ppm" regarding the composition indicate "% by mass" and "ppm by mass", respectively, unless otherwise specified.

[0039] Si: 1.50~8.00% Silicon is an element necessary for increasing the resistivity of steel and improving iron loss. Silicon is also an element necessary for forming the forsterite film in the steel sheet of the present invention. However, if the amount of silicon is less than 1.50%, there is no effect, and if the amount of silicon exceeds 8.00%, the workability of the steel deteriorates and rolling becomes difficult. For this reason, the amount of silicon is limited to 1.50 to 8.00%. The amount of silicon is preferably 2.50% or more, and is preferably 4.50% or less.

[0040] Mn: 0.02 to 1.00% Mn is an element necessary for improving hot workability. However, if the Mn content is less than 0.02%, there is no effect, and if it exceeds 1.00%, the magnetic flux density of the product sheet decreases. Therefore, the Mn content is set to 0.02 to 1.00%. The Mn content is preferably 0.04% or more, and 0.20% or less.

[0041] Co: 0.005 to 0.050% For the reasons mentioned above, it is essential that Co is contained in an amount in the range of 0.005 to 0.050%. The Co amount is preferably 0.006% or more, and more preferably 0.008% or more. The Co amount is preferably 0.020% or less, and more preferably 0.015% or less.

[0042] The base steel sheet of the grain-oriented electrical steel sheet of the present invention may contain, in addition to the above-mentioned basic components (Si, Mn, and Co), C (e.g., 0.020 to 0.100%), Al (e.g., 0.002 to 0.040%), and N (e.g., 0.002 to 0.015%). The base steel sheet may also optionally contain S (e.g., 0.020% or less) and / or Se (e.g., 0.040% or less). The base steel sheet of the grain-oriented electrical steel sheet of the present invention may contain, in addition to the above-mentioned components, the following components (elements) as necessary.

[0043] Specifically, for the purpose of improving the magnetic properties, the base steel sheet contains the following: Sn: (more than 0%) 0.500% or less, Cr: (more than 0%) 0.500% or less, Cu: (more than 0%) 0.50% or less, Ni: (more than 0%) 0.50% or less, Bi: (more than 0%) 0.500% or less, P: (more than 0%) 0.500% or less, Sb: (more than 0%) 0.500% or less, Mo: (more than 0%) 0.500% or less, B: (more than 0ppm) 25.0ppm One or more of the following may be added in combination: pm or less, Nb: (over 0%) 0.020% or less, V: (over 0%) 0.020% or less, As: (over 0%) 0.0200% or less, Zn: (over 0%) 0.020% or less, Pb: (over 0%) 0.0100% or less, W: (over 0%) 0.0100% or less, Ga: (over 0%) 0.0050% or less, and Ge: (over 0%) 0.0050% or less. That is, each of the above elements can be contained in the base steel sheet within the above upper limit range in order to further improve the magnetic properties. If the amount (content) of each element exceeds the upper limit, the development of secondary recrystallized grains may be inhibited, resulting in deterioration of the magnetic properties. The lower limit of each element does not need to be particularly limited, but is preferably within the following range. Sn: 0.005% or more, Cr: 0.005% or more, Cu: 0.01% or more, Ni: 0.01% or more, Bi: 0.005% or more, P: 0.005% or more, Sb: 0.005% or more, Mo: 0.005% or more, B: 0.1ppm or more, Nb: 0.001% or more, V: 0.001% or more, As: 0.0010% or more, Zn: 0.001% or more, Pb: 0.0001% or more, W: 0.0010% or more, Ga: 0.0001% or more and Ge: 0.0001% or more

[0044] In the base steel sheet, the balance other than the above-mentioned components (elements) is Fe and unavoidable impurities.

[0045] The above-mentioned composition is the composition of the base steel sheet, i.e., does not take into consideration the undercoat mainly composed of forsterite. In the present invention, the Ti content in the steel sheet having the undercoat mainly composed of forsterite, i.e., the Ti content in the entire base steel sheet and the undercoat, is limited to 0.0050 to 0.0200% for the above-mentioned reasons. The Ti content in the entire base steel sheet and the undercoat is preferably 0.0060% or more and preferably 0.0150% or less. In addition, the "main component" of the undercoating refers to the component that has the largest mass among the components that make up the undercoating.

[0046] Here, when the Ti content in the steel sheet having a base coating is limited to 0.0050 to 0.0200%, the Ti content in the base steel sheet is preferably 0.0030% or less. This is because, if the Ti content in the base steel sheet is 0.0030% or less, it is possible to suppress a significant deterioration in iron loss caused by the formation of Ti precipitates in the steel. On the other hand, the Ti content in the steel sheet having a base coating is set to 0.0050% or more. This is because, as described above, it is believed that the presence of a certain amount of Ti in the forsterite coating can improve the coating properties and improve eddy current loss, but if the Ti content is less than 0.0050%, this effect is presumed to be insufficient.

[0047] Furthermore, in the present invention, as described above, it is necessary to limit the range of parameters calculated from the hysteresis loss and iron loss of the product steel sheet. That is, the iron loss W 17 / 50 Hysteresis loss Wh 17 The ratio of R17 (=Wh 17 / W 17 / 50 ) and the iron loss W when excited at 1.9T 19 / 50 Hysteresis loss Wh 19 Ratio of R19 (=Wh 19 / W 19 / 50) must satisfy the relationship 0.30≦R17≦R19. These values ​​can be measured using the methods specified in JIS C2550-1. Note that in order to match the hysteresis loss with the iron loss at 50Hz, the hysteresis loss can be calculated by multiplying the energy loss in the iron core over one revolution of the hysteresis loop by 50, which is the excitation frequency.

[0048] Next, the manufacturing method of the directional magnetic steel sheet of the present invention will be described. The manufacturing method can be a method for manufacturing a general magnetic steel sheet. For example, a slab may be manufactured from molten steel with a predetermined composition adjustment by a normal ingot casting method or a continuous casting method, or a thin cast piece with a thickness of 100 mm or less may be manufactured by a direct casting method. The molten steel may be manufactured by a blast furnace method or an electric furnace method. Since it is difficult to add the various components that may be contained in the base steel sheet described above during the process, it is preferable to add them at the molten steel stage. The slab is heated and hot rolled by a normal method, or is hot rolled immediately after casting without heating. In the case of heating, a low temperature of 1300°C or less is effective for the purpose of reducing costs, since a composition system with a small amount of inhibitor components does not require high-temperature annealing to dissolve the inhibitor. In the case of heating, the temperature is preferably 1250°C or less.

[0049] Next, hot-rolled sheet annealing is performed as necessary. The temperature of hot-rolled sheet annealing is preferably about 950 to 1150°C. If it is 950°C or higher, the remaining unrecrystallized parts can be sufficiently suppressed, and if it is 1150°C or lower, excessive coarsening of the grain size after annealing can be suppressed, and the subsequent primary recrystallization texture can be made better. The temperature of hot-rolled sheet annealing is preferably 1000°C or higher, and preferably 1100°C or lower.

[0050] The steel sheet after hot rolling or hot-rolled sheet annealing is cold-rolled to the final sheet thickness by one cold rolling or two or more cold rollings with intermediate annealing in between. The annealing temperature of the intermediate annealing is preferably in the range of 900 to 1200°C. If the annealing temperature is 900°C or higher, the recrystallized grains after the intermediate annealing can be effectively prevented from becoming too fine, and further, the deterioration of the magnetic properties of the product sheet due to the reduction of Goss nuclei in the primary recrystallized structure can be effectively prevented. On the other hand, if the annealing temperature is 1200°C or lower, the excessive coarsening of the crystal grains can be prevented, as in the case of hot-rolled sheet annealing, and the primary recrystallized structure of the grain size can be improved.

[0051] The cold-rolled sheet having the final thickness is then subjected to primary recrystallization annealing, which also serves as decarburization annealing. When decarburization annealing is involved in the primary recrystallization annealing, the annealing temperature is preferably in the range of 800 to 900°C from the viewpoint of quickly progressing the decarburization reaction, and the atmosphere is preferably a moist atmosphere.

[0052] Thereafter, an annealing separator mainly made of MgO is applied, followed by purification annealing, which allows the secondary recrystallization structure to develop and the forsterite film to form. Here, "mainly made of MgO" means that the steel contains 75 mass% or more of MgO.

[0053] Furthermore, Ti can be effectively made to exist in the forsterite coating by adding a Ti compound to the annealing separator and by introducing a N2 atmosphere during purification annealing, which will be described later. However, Ti may also be made to exist in the forsterite coating by other methods.

[0054] Next, secondary recrystallization annealing (purification annealing) is performed. This purification annealing is preferably performed at 800°C or higher to induce secondary recrystallization, and from the viewpoint of purification, it is preferable to raise the temperature to a holding temperature of 1100°C or higher. The holding temperature is more preferably 1180°C or higher. The longer the holding time, the more purification progresses, but since shape deterioration due to high-temperature creep occurs, it is preferable to hold for 3 hours or more and 15 hours or less. After the purification annealing, it is preferable to wash with water, brush, or pickle in order to remove the attached annealing separator. In addition, from the viewpoint of obtaining the desired iron loss characteristics, it is preferable that in the temperature rise process of the purification annealing, the N2 atmosphere is used up to the first intermediate temperature (for example, a temperature selected from the range of 600 to 800°C), the N2 and H2 mixed atmosphere is used from the first intermediate temperature to the second intermediate temperature (for example, a temperature selected from the range of 1050 to 1150°C), and the H2 atmosphere is used from the second intermediate temperature to the holding temperature.

[0055] Then, flattening annealing is performed to correct the shape, which is effective in reducing iron loss. When steel sheets are used in a laminated state, it is effective to apply an insulating coating to the surface of the steel sheet before or after flattening annealing in order to improve iron loss. As the insulating coating, a coating that can impart tension to the steel sheet in order to reduce iron loss is preferable. It is preferable to adopt a method of forming a coating by depositing an inorganic substance on the surface layer of the steel sheet by a tension coating application method using a binder, a physical vapor deposition method, or a chemical vapor deposition method, because these methods have excellent coating adhesion and a significant effect of reducing iron loss. EXAMPLES

[0056] The present invention will be specifically described below with reference to examples, although the present invention is not limited thereto.

[0057] Example 1 Steel slab A···C: 0.070%, Si: 3.55%, Mn: 0.07%, Al: 0.0080%, N: 0.0050%, Co: 0.012%, Mo: 0.026%, Ti: 0.025%, and the balance is Fe and unavoidable impurities. Steel slab B···C: 0.072%, Si: 3.51%, Mn: 0.07%, Al: 0.0080%, N: 0.0047%, Co: 0.011%, Mo: 0.025%, Ti: 0.0025%, and the balance is Fe and unavoidable impurities. Steel slab C···C: 0.072%, Si: 3.49%, Mn: 0.07%, Al: 0.0090%, N: 0.0051%, Co: 0.002%, Mo: 0.025%, Ti: 0.024%, and the balance is Fe and unavoidable impurities. Steel slab D: C: 0.068%, Si: 3.48%, Mn: 0.07%, Al: 0.0090%, N: 0.0050%, Co: 0.008%, Mo: 0.022%, Ti: 0.0010%, and the balance is Fe and unavoidable impurities. The above steel slabs A to D were each produced by continuous casting, and after slab heating at 1200°C for 40 minutes, they were finished to a thickness of 2.2 mm by hot rolling. After that, they were hot-rolled and annealed in a N2 atmosphere at 1000°C for 60 seconds. Then, they were cold-rolled to a thickness of 0.23 mm, and further decarburization annealed at 850°C for 90 seconds in a humid atmosphere of 60% H2-40% N2 with a dew point of 60°C.

[0058] Next, an annealing separator mainly composed of MgO (MgO: 97% by mass) was applied to the surface of the base steel sheet after decarburization annealing, and the steel was held at 1100°C for 25 hours, followed by purification annealing at 1200°C for 10 hours. During this temperature rise process, the atmosphere was N2 from room temperature to 700°C, atmospheres with various N2 and H2 mixture ratios were used from 700°C to 1100°C, and H2 atmosphere from 1100°C (start of holding) to 1200°C (end of holding). Furthermore, an Ar atmosphere was used during cooling.

[0059] The Ti content (the total Ti content in the base steel sheet and the undercoat film) of the thus obtained sample, i.e., the steel sheet having the undercoat film mainly composed of forsterite, was measured according to the method specified in JIS G1223. The results are shown in Table 1.

[0060] An insulating coating mainly composed of magnesium phosphate and silica was applied to the undercoat of the steel sheet. 17 / 50 (Iron loss when excited up to 1.7T at 50Hz) and W 19 / 50 (Iron loss when excited up to 1.9T at 50Hz) and hysteresis loss Wh 17 (Hysteresis loss when excited up to 1.7T) and Wh 19 (hysteresis loss when excited up to 1.9T) was measured according to the method specified in JIS C2550-1. 17 / W 17 / 50 (i.e. R17), and Wh 19 / W 19 / 50 (i.e. R19) are also shown in Table 1.

[0061] Furthermore, in order to measure the Co and Ti contents in the base steel sheet, a part of the obtained sample was immersed in a 10% hydrochloric acid solution at 80°C for 180 seconds to remove the undercoat, and the sample was subjected to measurements according to the methods specified in JIS G1222 and JIS G1223. The measurement results are shown in Table 1.

[0062] Next, a three-phase three-leg model transformer was created from the sample with the insulating coating, with an external shape of 500 mm square and a plate width of 100 mm for each leg and yoke, and the iron loss of the model transformer W 17 / 50 The iron loss of the model transformer was measured (when excited to 1.7T at 50Hz). The number of laminated samples was 50, with two laminated sheets stacked alternately. The building factor F17 of the model transformer was calculated by multiplying the iron loss of the model transformer by WT 17 / 50 The iron loss of the sample W 17 / 50 Divided by (WT 17 / 50 / W 17 / 50 The results are shown in Table 1.

[0063] [Table 1]

[0064] As is clear from Table 1, it can be seen that the samples (grain-oriented electrical steel sheets) according to the present invention have good core loss characteristics (building factor).

[0065] Example 2 A steel slab containing the components shown in Table 2, with the balance being Fe and unavoidable impurities, was produced by continuous casting, and after slab heating at 1410°C for 20 minutes, it was finished to a thickness of 2.4 mm by hot rolling. Then, it was annealed at 1100°C for 20 seconds in a N2 atmosphere. Next, it was cold rolled to a thickness of 1.5 mm, and further annealed at 900°C for 100 seconds in a 25%H2-75%N2 atmosphere. Then, it was cold rolled to a thickness of 0.23 mm, and further decarburization annealed at 825°C for 150 seconds in a humid atmosphere of 40%H2-60%N2 with a dew point of 45°C.

[0066] [Table 2]

[0067] Next, an annealing separator mainly composed of MgO (MgO: 88 mass%) was applied to the surface of the base steel sheet after decarburization annealing. The annealing separator was prepared by adding 5 parts by mass of perhydrated TiO2 powder, which was obtained by adding TiO2 powder to hot water at 50°C and stirring for 24 hours.

[0068] Furthermore, purification annealing was performed by holding at 1200°C for 10 hours. During this, the heating rate up to 1200°C was 15°C / h, and further, during the heating process, an N2 atmosphere was used from room temperature to 700°C, an atmosphere with various mixture ratios of N2 and H2 was used from 700°C to 1100°C, and an H2 atmosphere was used from 1100°C to 1200°C. The holding time was an H2 atmosphere, and the cooling time was an Ar atmosphere.

[0069] The Ti content (the total Ti content in the base steel sheet and the undercoat) of the thus obtained sample, i.e., the steel sheet having the undercoat mainly composed of forsterite, was measured according to the method specified in JIS G 1223. The measurement results are shown in Table 3.

[0070] An insulating coating mainly composed of magnesium phosphate and silica was applied to the undercoat of the steel sheet. 17 / 50 (Iron loss when excited up to 1.7T at 50Hz) and W 19 / 50 (Iron loss when excited up to 1.9T at 50Hz) and hysteresis loss Wh 17 (Hysteresis loss when excited up to 1.7T) and Wh 19 (hysteresis loss when excited up to 1.9T) was measured according to the method specified in JIS C2550-1. 17 / W 17 / 50 (i.e. R17), and Wh 19 / W 19 / 50 (i.e. R19) are also shown in Table 3.

[0071] Furthermore, in order to measure the Co and Ti contents in the base steel sheet, a part of the obtained sample was immersed in a 10% hydrochloric acid solution at 80°C for 180 seconds to remove the undercoat, and the sample was subjected to measurements according to the methods specified in JIS G1222 and JIS G1223. The measurement results are shown in Table 3.

[0072] Next, a three-phase three-leg model transformer was created from the sample with the insulating coating, with an external shape of 500 mm square and a plate width of 100 mm for each leg and yoke, and the iron loss of the model transformer W 17 / 50 The iron loss of the model transformer was measured (when excited to 1.7T at 50Hz). The number of laminated samples was 50, with two laminated sheets stacked alternately. The building factor F17 of the model transformer was calculated by multiplying the iron loss of the model transformer by WT 17 / 50 The iron loss W of the sample 17 / 50 Divided by (WT 17 / 50 / W 17 / 50 The results are shown in Table 3.

[0073] [Table 3]

[0074] As is clear from Table 3, it can be seen that the samples (grain-oriented electrical steel sheets) according to the present invention have good core loss characteristics (building factor).

Claims

1. A grain-oriented electrical steel sheet comprising a base steel sheet containing 1.50 to 4.50 mass% Si, 0.02 to 1.00 mass% Mn, 0.005 to 0.050 mass% Co, with the balance being Fe and unavoidable impurities, and a base coating containing forsterite as a main component and formed on a surface of the base steel sheet, the Ti content in the base steel sheet is 0.0034% by mass or less, and the Ti content in the base steel sheet and the undercoating as a whole is 0.0050 to 0.0200% by mass, Iron loss W when excited at 1.7T 17 / 50 Hysteresis loss Wh 17 Ratio of Wh 17 / W 17 / 50 When R is 17 and excited at 1.9T, the iron loss W 19 / 50 Hysteresis loss Wh 19 Ratio of Wh 19 / W 19 / 50 A grain-oriented electrical steel sheet that satisfies the following formula (1), where R19 is the grain size. 0.30≦R17≦R19 ... (1)

2. The grain-oriented electrical steel sheet according to claim 1, wherein the Ti content in the base steel sheet is 0.0030 mass% or less.

3. The grain-oriented electrical steel sheet according to claim 1 or 2, further comprising an insulating coating on a surface of the undercoating.

4. 3. The grain-oriented electrical steel sheet according to claim 1 or 2, wherein the base steel sheet further contains one or more selected from Sn: 0.500 mass% or less, Cr: 0.500 mass% or less, Cu: 0.50 mass% or less, Ni: 0.50 mass% or less, Bi: 0.500 mass% or less, P: 0.500 mass% or less, Sb: 0.500 mass% or less, Mo: 0.500 mass% or less, B: 25.0 mass ppm or less, Nb: 0.020 mass% or less, V: 0.020 mass% or less, As: 0.0200 mass% or less, Zn: 0.020 mass% or less, Pb: 0.0100 mass% or less, W: 0.0100 mass% or less, Ga: 0.0050 mass% or less, and Ge: 0.0050 mass% or less.

5. 4. The grain-oriented electrical steel sheet according to claim 3, wherein the base steel sheet further contains one or more selected from Sn: 0.500 mass% or less, Cr: 0.500 mass% or less, Cu: 0.50 mass% or less, Ni: 0.50 mass% or less, Bi: 0.500 mass% or less, P: 0.500 mass% or less, Sb: 0.500 mass% or less, Mo: 0.500 mass% or less, B: 25.0 mass ppm or less, Nb: 0.020 mass% or less, V: 0.020 mass% or less, As: 0.0200 mass% or less, Zn: 0.020 mass% or less, Pb: 0.0100 mass% or less, W: 0.0100 mass% or less, Ga: 0.0050 mass% or less, and Ge: 0.0050 mass% or less.

Citation Information

Patent Citations

  • Transformer silicon steel sheet and preparation method thereof

    CN108456829A

  • JP1965-015644B

  • hifunsaibutsushitsuofunsaisurutamenoshindomiru

    JP1976013469A

  • Novel precursor drug of biological activator containing mercapto group

    JP1982002252A

  • Air bag device

    JP1994072266A